2011
DOI: 10.1104/pp.110.167163
|View full text |Cite
|
Sign up to set email alerts
|

Proline Dehydrogenase Contributes to Pathogen Defense in Arabidopsis      

Abstract: l-Proline (Pro) catabolism is activated in plants recovering from abiotic stresses associated with water deprivation. In this catabolic pathway, Pro is converted to glutamate by two reactions catalyzed by proline dehydrogenase (ProDH) and Ɗ1-pyrroline-5-carboxylate dehydrogenase (P5CDH), with Ɗ1-pyrroline-5-carboxylate (P5C) as the intermediate. Alternatively, under certain conditions, the P5C derived from Pro is converted back to Pro by P5C reductase, thus stimulating the Pro-P5C cycle, which may generate rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
173
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(182 citation statements)
references
References 75 publications
(129 reference statements)
6
173
0
3
Order By: Relevance
“…High proline accumulation in diseased tissue probably is due to pathological disorders (Smimoff & Cumbes 1989). Cecchini et al (2011) showed that L-proline catabolism is activated in plants during recovering process.…”
Section: Resultsmentioning
confidence: 99%
“…High proline accumulation in diseased tissue probably is due to pathological disorders (Smimoff & Cumbes 1989). Cecchini et al (2011) showed that L-proline catabolism is activated in plants during recovering process.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] In addition, the oxidation of Argand/or Orn-derived polyamines and the metabolism of Pro contribute to the production of reactive oxygen species and to the development of hypersensitive cell death following elicitor treatment or inoculation with avirulent bacteria. 10,11 Further, the formation of acetylated amino acids and phytohormone-amino acid conjugates can mediate or negatively regulate plant defense signaling and pathogen resistance. [12][13][14] Also, enhanced production of particular amino acids can directly impact plant resistance to specific pathogen types.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that several enzymes of plant primary metabolism, Glc-6-P dehydrogenase (Scharte et al, 2005), malic enzyme Voll et al, 2012), and Pro dehydrogenase (Cecchini et al, 2011), provide the cytosol with reducing equivalents that are required for the effective production of reactive oxygen species and can directly support induced plant defenses with reducing power. In addition, several reports reinforce the ideas that (1) the balance between extracellular Suc and hexose is perceived by the host (Biemelt and Sonnewald, 2006, and refs.…”
mentioning
confidence: 99%